5‐Hydroxy‐7‐methoxyflavone derivatives from Kaempferia parviflora induce skeletal muscle hypertrophy. Issue 1 (20th November 2018) - Ono, Shintaro; Yoshida, Naoki; Maekawa, Daisuke; Kitakaze, Tomoya; Kobayashi, Yasuyuki; Kitano, Takehiro; Fujita, Takanori; Okuwa‐Hayashi, Hirotaka; Harada, Naoki; Nakano, Yoshihisa; Yamaji, Ryoichi
Abstract: Skeletal muscle plays a critical role in locomotion and energy metabolism. Maintenance or enhancement of skeletal muscle mass contributes to the improvement of mobility and prevents the development of metabolic diseases. The extracts from Kaempferia parviflora rhizomes contain at least ten methoxyflavone derivatives that exhibit enhancing effects on ATP production and glucose uptake in skeletal muscle cells. In the present study, we investigated the effects of ten K. parviflora ‐derived methoxyflavone derivatives (six 5, 7‐dimethoxyflavone (DMF) derivatives and four 5‐hydroxy‐7‐methoxyflavone (HMF) derivatives) on skeletal muscle hypertrophy. Murine C2C12 myotubes and senescence‐accelerated mouse‐prone 1 (SAMP1) mice treated with methoxyflavones were used as experimental models to determine the effects of HMF derivatives on myotube diameter and size and muscle mass. The four HMF derivatives, but not the six DMF derivatives, increased myotube diameter. The 5‐hydroxyflavone, 7‐methoxyflavone, and 5, 7‐dihydroxyflavone had no influence on myotube size, a result that differed from HMF. Dietary administration of the mixture composed of the four HMF derivatives resulted in increase in the soleus muscle size and mass in SAMP1 mice. HMF derivatives also promoted protein synthesis in myotubes, and treatment with the intracellular Ca 2+ chelator BAPTA‐AM, which depletes intracellular Ca 2+ levels, inhibited this promotion. Furthermore, BAPTA‐AM inhibited HMF‐promoted protein synthesis even when myotubes were incubated in Ca 2+ ‐free medium. These results indicate that HMF derivatives induce myotube hypertrophy and that both the 5‐hydroxyl group and the 7‐methoxy group in the flavones are necessary for myotube hypertrophy. Furthermore, these results suggest that HMF‐induced protein synthesis requires intracellular Ca 2+, but not extracellular Ca 2+ . Abstract : The structure–activity relationship of the 5‐hydroxy and 7‐methoxy groups of the methoxyflavones was determined on the diameter of the short axis of myotubes and the expression level of myosin heavy chain (MyHC). 5‐Hydroxy‐7‐methoxyflavone (5‐OH‐7‐OCH3 ), but not 5, 7‐dimethoxyflavone (5, 7‐diOCH3 ), 5‐hydroxyflavone (5‐OH), 7‐methoxyflavone (7‐OCH3 ), and 5, 7‐dihydroxyflavone (5, 7‐diOH), increased the myotubes size and the expression level of MyHC.